FAKTOR RISIKO YANG MEMPENGARUHI NILAI GLASGOW COMA SCALE (GCS)PADA PASIEN STROKE PERDARAHAN DENGAN HIPERTENSI DI RSUP DR. SARDJITO - , REZA PANDU AJI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Stroke is the 3rd cause of death in the world after cardiovascular disease and cancer. The world prevalence of stroke is 30,7 million people per year, while the incidence reach 9 million people per year. There are 2 types of stroke: ischemic stroke and hemorrhagic stroke. Between the two, hemorrhagic stroke is less frequent but have a higher mortality late. One of the modifiable risk factor for hemorrhagic stroke is hypertension which has a signicant effect on stroke with every increasi of systolic blood pressure being proportional to increase of risk. This research aim to see if there is an effect of risk factors of hemorrhagic stroke towards GCS score in hemorrhagic stroke patients with hypertension in Dr. Sardjito Central Hospital. Aim:To see if there is a risk factor that affect to score of GCS in hemorrhagic stroke patients in Dr. Sardjito Central Hospital. Method: Research subjects are hemorrhagic stroke patients diagnosed with hypertension by the time of hospital admission. Samples are chosen based on inclusion and exclusion criterias. The data is obtained by consecutive sampling using medical records of hemorrhagic stroke patients admitted to hospital during the period of January 2012 to December 2012. Research tools that are used are medical record form, containing: name, age, gender, smoking status, hypercholesterolemia status, diabetes status, and whether the hypertension is controlled or not controlled based on the use of antihypertensive drugs. The analytical technique used is Mann-Whitney Test. Result: There are two risk factors combination with p<0,1 that is the combination of patients age >50 with smoking history (n=9) with median GCS score of 4 (3-15) with p=0,03 and combination of patients age >50 with uncontrolled hypertension and smoking history (n=7) with median GCS score of 4 (3-15) with p=0,08. Conclusion: Combination of hypertension patients age >50 with history of smoking and combination of uncontrolled hypertension patients age >50 with history of smoking are the factors that affect the decrease of GCS score in the incidence of hemorrhagic stroke.